Recent Advances in Integrated Vibration Sensing and Communication in Digital Subcarrier Multiplexing Systems - Bang Yang; Jianwei Tang; Linsheng Fan; Yaguang Hao; Chen Cheng; Shangyi Wang; Shuang Gao; Zhongliang Sun; Junpeng Liang; Weisheng Hu; Yanfu Yang; Jinlong Wei (Photonics)
Digital subcarrier multiplexing (DSCM) systems offer flexibility and software configurability, making them promising for point-to-multipoint (P2MP) communications. Meanwhile, DSCM systems exhibit enhanced communication damage tolerance and capabilities for damage monitoring and compensation. These capabilities include tolerance to equalized enhanced phase noise (EEPN) and high-speed Polarization State (SOP) tracking. The subcarrier intervals in DSCM systems naturally allow the insertion of pilot or training sequences. This facilitates enhanced communication functionality and integrated sensing capabilities. This review article summarizes the principles and schemes of integrated communication and sensing in DSCM systems. It analyzes performance in communication enhancement and sensing integration. Finally, it discusses unresolved technical challenges and future technological prospects.